Dissecting risk adjusted return through the sustainable lense - Mettävainio,Isak; Bergo,Erik (2024)
In this thesis, the impact that sustainability ratings have on risk adjusted performance metrics such as the Sharpe and Treynor ratio will be evaluated. The authors employ the use of Morningstar's sustainability ratings, ranging from one to five “globes” in their measure of sustainability. An array of different types of funds will be used, these include equity, mutual, index and interest funds. Findings point towards that funds with lower sustainability ratings, especially those with two globes consistently show statistical significance regarding their positive impact on these performance metrics, although no clear patterns emerge regarding ratings above or below two. These findings are then analyzed through the lens of the efficient market hypothesis (EMH) as well as modern portfolio theory (MPT). However, the results are not uniform across all rating levels as well as all specifications of the models. Limitations include sample size along with the availability of financial data such as historical records of sustainability ratings. Future research can further investigate this relationship by the use of longitudinal studies, thereby being able to draw more robust conclusions along with what the impact of changing ratings has on financial performance.
Keywords: ESG; financial performance; sustainability; funds; risk adjusted return